THE ESSENCE OF THE POTENTIAL OF THE AGRICULTURAL ENTERPRISE AND THE DIAGNOSTICS OF ITS FORMATION - Колач, Світлана; Василина, Орися; Березівський, Зеновій; Періг, Юрій (SWorldJournal, 2024)
The work examines the essence of the formation and development of the potential of an agricultural enterprise, its structure and properties, which are the basis of its effective use. The aspiration to a high level of utilization of the potential of econom